2022
DOI: 10.1002/advs.202201378
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Viral Entry Inhibitors as Broad‐Spectrum First‐Line Antivirals with Activity against SARS‐CoV‐2

Abstract: Inhibitorsof viral cell entry based on poly(styrene sulfonate) and its core-shell nanoformulations based on gold nanoparticles are investigated against a panel of viruses, including clinical isolates of SARS-CoV-2. Macromolecular inhibitors are shown to exhibit the highly sought-after broad-spectrum antiviral activity, which covers most analyzed enveloped viruses and all of the variants of concern for SARS-CoV-2 tested. The inhibitory activity is quantified in vitro in appropriate cell culture models and for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…[ 62 , 63 , 64 ] In this study, combined with the excellent biocompatibility of Ti 3 C 2 nanosheets, MPS was modified on the surface of nanosheets, enabling the functionally modified nanocomposite to have significant antiviral activity and allowing the functionalized Ti 3 C 2 nanosheets to inhibit the proliferation of viruses with heparan sulfate as receptor or co‐receptor for the first time. In general, the nanocomposite entry inhibitor can minimize the effects of viral mutation and host toxicity without conferring immunogenicity, [ 65 , 66 , 67 ] and Ti 3 C 2 ‐Au‐MPS nanocomposites may also have relevant properties. Current antiviral research models mainly consider the life cycle of viruses through viral adsorption, invasion, replication, assembly, and release of new viruses, [ 61 , 68 , 69 ] and Ti 3 C 2 ‐Au‐MPS nanocomposites inhibit viral proliferation at every stage in the intial stage of the cycle.…”
Section: Resultsmentioning
confidence: 99%
“…[ 62 , 63 , 64 ] In this study, combined with the excellent biocompatibility of Ti 3 C 2 nanosheets, MPS was modified on the surface of nanosheets, enabling the functionally modified nanocomposite to have significant antiviral activity and allowing the functionalized Ti 3 C 2 nanosheets to inhibit the proliferation of viruses with heparan sulfate as receptor or co‐receptor for the first time. In general, the nanocomposite entry inhibitor can minimize the effects of viral mutation and host toxicity without conferring immunogenicity, [ 65 , 66 , 67 ] and Ti 3 C 2 ‐Au‐MPS nanocomposites may also have relevant properties. Current antiviral research models mainly consider the life cycle of viruses through viral adsorption, invasion, replication, assembly, and release of new viruses, [ 61 , 68 , 69 ] and Ti 3 C 2 ‐Au‐MPS nanocomposites inhibit viral proliferation at every stage in the intial stage of the cycle.…”
Section: Resultsmentioning
confidence: 99%
“…18 Both natural and synthetic sulfated/sulfonated materials have been shown to act as HSPG-mimics and bind to viruses; their antiviral properties has been known for many years. [19][20][21][22][23][24] Consequently, a wide array of materials, such as sulfonated nanoparticles, 22,25,26 both natural (such as sulfonated polysaccharides from seaweed) and synthetic polymers, [27][28][29] have been demonstrated as being broad-spectrum antivirals.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Recently, Groß and co-workers demonstrated the use of poly(styrene sulfonate) (PSS) decorated gold nanoparticles (AuNP) that showed broad-spectrum antiviral activity against a range of enveloped viruses, such as: SARS-COV-2, Zika, respiratory syncytial virus (RSV) and HIV-1. 26 They showed that over a broad range of PSS molecular weights, the nanoparticles showed: broad-spectrum antiviral activity, biocompatibility, and that the antiviral activity was not dependent on the size of the AuNP core itself but rather the size of the polymer. However, they reported that all of the PSS coated AuNPs they studied were virustatic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This class of viruses infect host cells by binding of the spike protein to cellular entry receptors such as angiotensin-converting enzyme 2 (ACE2) for SARS-CoV and SARS-CoV-2. , Upon attachment, viruses enter cells via endocytosis and subsequently replicate their RNA . By developing polymers that bind to the viral spike glycoprotein, viral attachment onto the cell receptors could be prevented effectively. , Anionic polymers were shown to be potential candidates, as the computational ligand docking analysis provided evidence that heparan sulfate interacted with the spike glycoprotein of SARS-CoV-2. From the safety perspective, anionic polymers usually also show lower cytotoxicity and higher biocompatibility than their cationic counterparts, partly due to the stronger interaction of cationic polymers with serum proteins in the in vivo environment. , Most antiviral polymers currently available are not easily degraded in a physiological environment, , resulting in bioaccumulation that may lead to a health and environmental concern. With a highly biocompatible and biodegradable backbone, polycarbonates therefore represent an attractive class of polymers for biological applications. …”
Section: Introductionmentioning
confidence: 99%